Concentration-alternating frequency response: A new method for studying polymer electrolyte membrane fuel cell dynamics. (20th July 2017) - Sorrentino, Antonio; Vidakovic-Koch, Tanja; Hanke-Rauschenbach, Richard; Sundmacher, Kai
Abstract : Graphical abstract: Abstract: In this work, the concentration-alternating frequency response analysis (cFRA) is proposed as a new method to study the dynamics of open electrochemical systems. The cFRA implies the perturbation of the electrochemical system through a feed characterized by a periodic concentration of a certain reactant. The most suitable detectable electrical output variable (potantial or current density) depends on the operating condition under which the experiment is performed. As illustrative example, a transient model accounting for the essential dynamic processes occurring in polymer electrolyte membrane fuel cells (PEMFC) is derived, and used to investigate the valuable insights obtainable from the cFRA spectra. Additionally, a sensitivity analysis is accomplished by use of sensitivity coefficients in order to estimate which model parameters can be better identified from EIS or from cFRA. It is shown that cFRA displayes a significantly higher sensitivity than EIS for kinetic parameters. Moreover, a detailed analysis of the feasibility of the new technique is performed to identify appropriate operating conditions. In conclusion, cFRA can be regarded as an innovative and valuable tool for PEMFC identification.